On the rigidity of ℂℙ2n × ℂℙ1 - Hall, Stuart James (Complex manifolds (Warsaw, Poland), 2025)
We revisit Koiso’s original examples of rigid infinitesimally deformable Einstein metrics. We show how to compute Koiso’s obstruction to the integrability of the infinitesimal deformations on using completely elementary complex differential geometry.